Array‐comparative genomic hybridization analysis in patients with Müllerian fusion anomalies. Issue 3 (5th February 2018) - Ledig, S.; Tewes, A.C.; Hucke, J.; Römer, T.; Kapczuk, K.; Schippert, C.; Hillemanns, P.; Wieacker, P.
Abstract : Fusion anomalies of the Müllerian ducts are associated with an increased risk for miscarriage and premature labor. In most cases polygenic‐multifactorial inheritance can be assumed but autosomal‐dominant inheritance with reduced penetrance and variable manifestation should be considered. We performed array‐comparative genomic hybridization (CGH) analysis in a cohort of 103 patients with Müllerian fusion anomalies. In 8 patients we detected microdeletions and microduplications in chromosomal regions 17q12, 22q11.21, 9q33.1, 3q26.11 and 7q31.1. The rearrangement in 17q12 including LHX1 and HNF1β as well as in 22q11.21 have already been observed in MRKHS (Mayer‐Rokitansky‐Küster‐Hauser syndrome). In summary, we (1) detected causative micro‐rearrangements in patients with Müllerian fusion anomalies, (2) show that Müllerian fusion anomalies and MRKHS may have a common etiology, and (3) identified new candidate genes for Müllerian fusion anomalies. Abstract :